Computer simulation of a submerged membrane bioreactor treating high COD industrial wastewater - Palogos, Ioannis; Babatsouli, Panagiota; Costa, Costas; Kalogerakis, Nicolas (Frontiers in Environmental Science, 2014)
A dynamic model was developed to simulate the behavior of the biological processes taking place in a membrane bioreactor (MBR) pilot plant treating industrial wastewater at the Heraklion Industrial Park including the cake development on the membrane surface. The modified extended CES-ASM3 model has been used. Hydrolysis rates of the soluble microbial products have been added. Membrane fouling was taken into account and trans membrane pressure (TMP) was modeled and compared to experimental data. Simulation results are presented for the operation period between February 2012 and May 2013 and the prediction ability of the model is shown through the computation of the mean relative error of each measured state variable. Overall, the model estimates match the experimental data satisfactorily, as they follow similar trends while for all input variables their mean value was used as a constant input in the simulations. The operation of the MBR was conducted at three different sludge retention times.